Role and Challenges of SSIs in Changing Business Environment - Thapliyal, A. B (Journal of Commerce and Trade, 2012)
The small scale Industries (SSIs) sector has emerged as a dynamic sector of the Indian economy. This sector is important not only for its contribution to GDP but also for its continuous increase in exports and generating employment. The growth of this sector over the decades after independence is really breathtaking. The SSI sector happens to be at crossroads at present juncture. The new economic conditions have thrown up new challenges in the form of competition and opportunities for scaling new heights. The small industries are now not only have to face competition from Indian companies, but are poised to face stiff competition from multinational companies also. So, in the context of economic reforms and globalization the SSIs must be competitive for their survival and growth . There is an imminent need also to upgrade its technology as per global business environment.